Fabrication and Testing of Friction Stir Welds - Siddharth Sajan George (International Journal of Advanced Science and Technology, 2020)
Friction stir welding (FSW) is a solid-state joining process that uses a non-consumable tool to join two facing workpieces without melting the workpiece material. Heat is generated by friction between the rotating tool and the workpiece material, which leads to a softened region near the Friction Stir Welding tool. While the tool is traversed along the joint line, it mechanically intermixes the two pieces of metal, and forges the hot and softened metal by the mechanical pressure, which is applied by the tool, much like joining clay, or dough. Majority of the heat and pressure is generated due to the downward pressure applied by the tool shoulder as it traverses through the material, helping to heat and soften the metal. It is primarily used on wrought or extruded Aluminium and particularly for structures which need very high weld strengths. Friction Stir Welding is also found in modern shipbuilding, trains, and aerospace applications. Research and testing were conducted on the Friction Stir Welds in order to determine if the welds produced were at least as strong if not stronger than the base metal. To test the feasibility and the strength of the weld produced through Friction Stir Welding, welds were produced in alloys of Aluminium and Magnesium manually using a Vertical Milling Machine and automatically with the help of a CNC machine. The welds produced were then subjected to various tests such as Microstructure and Microhardness Testing, Tensile Testing and Bending Testing.